GENETIC VARIATION IN LENTIL GENOTYPES BY MORPHO-AGRONOMIC TRAITS AND RAPD-PCR - N. Abdul-Razzak Tahir; D.A. Omer (Journal of Animal and Plant Sciences, 2017)
In Iraq, one of the most common problems in lentil crop is the narrow genetic background, which must be explored to increase the production of lentil. Agro-morphological and molecular characterization were performed to evaluate the genetic diversity among nine lentil genotypes. Lentil genotypes were planted during crop season 2014/2015.According to statistical analysis, the lentil genotypes significantly differed in all studied traits. Based on phenological performance, genotypes Sulaimani-1, Sulaimani-2, and Sulaimani-3 were the genotypes that need the maximum number of days for 50% flowering and physiological maturity. Genotype FLIP 2007-69L excelled other genotypes for pod weight and seed yield. Based on the scatter plot of all agro-morphological data, PC1 (F1) and PC2 (F2) scores computed for 44.338 and 22.200% of the total variance, respectively. According to ascending hierarchical clustering, the analysis revealed three major clusters. Eighteen RAPD primers amplified 92 polymorphic bands. Primer OPA10showed the highest number of polymorphic fragments (8), whileOPA09 produced the lowest (1).Maximum gene diversity (0.840) and PIC (0.819) were found at the loci NOCOD04, OPA10, and OPN07 while the minimum gene diversity (0.444) and PIC (0.346) observed at the locus OPA09.According to dendrogram and PCA, nine genotypes were discriminated into three main clusters. The lowest dissimilarity value was 0.313 (between FLIP 2006-20L and FLIP 2007-69L), whereas the highest distance (0.803) was between FLIP 2007-53L and Sulaimani-2. AMOVA indicated the high variation (60%) within lentil genotypes; however, considerable variation (40%)was recorded between Local and ICARDA populations.
Keywords: Genetic diversity; Clustering; Agro-morphological traits; RAPD marker